Udødeligheden – en begrebshistorisk skitse - Lysemose, Kasper (Dansk Teologisk Tidsskrift, 2010)
Immortality apparently plays a minor role in the existential and religious self-understanding of modernity. The concept itself seems antiquated and obsolete. In this situation the best way to approach the concept is through the conceptual history of immortality. This is done in three steps: immortality is firstly considered as a theoretical problem, secondly as a practical postulate, and finally as an existential task. It is a further aim of the article to provide some conditions for a philosophically informed and historically saturated reflection on the significance which immortality might still have. Such a reflection is not itself pursued in the article. But a possible direction is pointed out by addressing Kant’s and Blumenberg’s notions of immortality as respectively a practical postulate and a trial of memory.